ANALISIS PRILAKU KONSUMSI MUSLIM PADA BULAN RAMADHAN - Hareastoma Hareastoma (Imara: JURNAL RISET EKONOMI ISLAM, 2019)
This study aims to analyze the patterns of Muslim consumption behaviors in the Ramadhan month around Jambi. A multiple linear regression analysis model is used to see the factors influencing the consumption behaviors. The finding shows that cultural and religiosity variables are the dominant factors influencing the pattern of Muslim consumption behaviors in the Ramadhan month. From the statistic results of SPSS verse 22, it was found the coefficient of determination (adjusted R2) obtained at 0.164. (16.4%). It reflects that 16.4% of consumption patterns influencing by the Cultural, Social, Religiusity and Psychology variables while the remaining 83.6% consumption patterns are influenced by unnecessary variables in this research.